Galcanezumab for the prevention of cluster headache. (2nd October 2020) - Giani, Luca; Proietti Cecchini, Alberto; Leone, Massimo
ABSTRACT: Introduction: Cluster headache (CH) is among the worst painful conditions. The available therapies are scarce and not specific, leaving many patients unsatisfied because of poor efficacy and/or tolerability. Patients not responding to common treatments are offered semi-invasive and invasive procedures with uncertain results. Based on the current understanding of CH pathophysiology, new possible therapeutic approaches come from drugs interfering with Calcitonin Gene Related Peptide (CGRP). Areas covered: After summarizing the evidence for CGRP involvement in CH pathophysiology, we review the published literature (PubMed) and information (clinicaltrials.gov, EudraCT, EMA and FDA websites) regarding a novel anti-CGRP monoclonal antibody, Galcanezumab, its pharmacological properties, development, and evidence for the treatment of CH. Publications regarding other indications (migraine) are considered for completeness and safety/tolerability profile. Expert opinion: In one randomized clinical trial, Galcanezumab has proven to be effective and safe as a preventive treatment in episodic CH, with a favorable tolerability profile offering a potential new option in the therapeutic arsenal. Inefficacy of galcanezumab in chronic CH as well as the inefficacy of another monoclonal antibody against CGRP (fremanezumab) in both episodic and chronic CH question the scalability of the drug in CH management. Further, studies comparing galcanezumab to the current standard treatments are highly desirable.